Optical properties of Au nanostructures obtained by pulsed UV laser irradiation of thin films - Grochowska, Katarzyna; Śliwiński, Gerard (Photonics Letters of Poland, 2011)
The particle size distribution, morphology and optical properties of the Au nanoparticle structures are investigated in relation to their preparation conditions. The structures are produced from thin Au films (10-20nm) sputtered on SiO2 glass substrate and annealed with several pulses (6ns) of laser radiation at 266nm and at fluencies in the range of 10?400mJ/cm2. The scanning electron microscopy (SEM) inspection reveals nearly homogeneously distributed, spherical gold particles with an average radius of 40nm. In the absorbance spectra of the nanostructures the broad peak centered at 550nm is ascribed to resonant absorption of surface plasmons (SPR). The peak position, halfwidth and intensity depend on the shape, size and size distribution of the nanostructured particles in agreement with literature. From peak intensities of the Raman spectra, recorded for Rhodamine 6G in the range of 300?1800cm-1, the relative signal enhancement for individual peaks (by a factor between 20 and 603) is estimated. Results confirm that the obtained structures are suitable for surface enhanced Raman spectroscopy (SERS) measurements and sensing. Full Text: PDF References: U. Kreibig, M. Vollmer, Optical properties of metal clusters (Berlin, Springer 1995) J. Vosburgh, R.H. Doremus, J. Non-Cryst. Sol. 349, 309 (2004) S.E. Imamova, A. Dikovska, N.N. Nedyalkov, P.A. Atanasov, M. Sawczak, R. Jendrzejewski, G. Sliwinski, M. Obara, "Laser nanostructuring of thin Au films for application in surface enhanced Raman spectroscopy", J. Optoel. Adv. Mat. 12, 500 (2010). [DirectLink] N.N. Nedyalkov, S.E. Imamova, P.A. Atanasov, M. Obara, "Near field localization mediated by a single gold nanoparticle embedded in transparent matrix: Application for surface modification", Appl. Surf. Sci. 255, 5125 (2009). [CrossRef] M.M. Alvarez, J.T. Khoury, T.G. Schaaff, M.N. Shafigullin, I. Vezmar, R.L. Whetten, "Optical Absorption Spectra of Nanocrystal Gold Molecules", J. Phys. Chem. B 101, 3706 (1997). [CrossRef] M.L. Theye, "Investigation of the Optical Properties of Au by Means of Thin Semitransparent Films", Phys. Rev. B 2, 3060 (1970). [CrossRef] C. Sonnichsen, Plasmons in metal nanostructures (University of Munich 2001). G. Li, H. Li, Y. Mo, X. Huang, and L. Chen, "Surface enhanced resonance Raman spectroscopy of rhodamine 6G adsorbed on silver electrode in lithium batteries", Chem. Phys. Lett. 330, 249 (2000). [CrossRef] M. Michaels, J. Jiang, L. Brus, "Ag Nanocrystal Junctions as the Site for Surface-Enhanced Raman Scattering of Single Rhodamine 6G Molecules", J. Phys. Chem. B 104, 11965 (2000). [CrossRef]